Mechanosynthesis of the multiferroic cubic spinel Co2MnO4: Influence of the calcination temperature - Santos, Maria Elenice dos [UNESP]; Castro, Alicia; Martinez, Inmaculada; Lisboa Filho, Paulo Noronha [UNESP]; Pena, Octavio (Elsevier B.V., 2014)
Multiferroic materials showing magnetoelectric coupling are required in various technological applications. Many synthetical approaches can be used to improve the magnetic and/or electrical properties, in particular when the materials exhibit cationic valence fluctuations, as in the Co2MnO4 cubic spinel. In this compound, Co and Mn ions are in competition at the tetrahedral and octahedral positions, depending on their various oxidation states. The Co2MnO4 was prepared following two techniques: by a soft chemical route based on a modified polymer precursor method, and by a mechanoactivation route. Both approaches yield polycrystalline powders, but their crystallites sizes and particles morphologies differ as a function of the calcination conditions. The magnetic characterization (ZFC/FC cycles, ordering temperatures, ferromagnetic coercive fields and saturation magnetizations) showed that the synthesis procedure influenced the physical properties of Co2MnO4 mainly through the size of the magnetic domains, which play an important role on the magnetic interactions between the Co/Mn cations. Crown Copyright (C) 2013 Published by Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Magnetic properties; Multiferroic materials; Mechanoactivation; Thermal treatment; Microstructure